The Impact of Cerebral Microbleeds Presence on Outcome Following Minor Stroke Treated With Antiplatelet Therapy - Sakuta, Kenichi; Yaguchi, Hiroshi; Sato, Takeo; Komatsu, Teppei; Sakai, Kenichiro; Mitsumura, Hidetaka; Matsushima, Satoshi; Iguchi, Yasuyuki (Frontiers in Neurology, 2020)
Background and Purpose— The relationship between cerebral microbleeds (CMBs) and prognosis in patients with ischemic stroke is still unclear. Our aim here was to verify the relationship between CMBs and functional outcomes in patients with minor ischemic stroke treated with antiplatelet therapy. Methods— We retrospectively reviewed consecutive patients with a non-cardiogenic minor ischemic stroke (NIHSS <4 on admission) who underwent initial brain magnetic resonance imaging within the first 48 hours following symptom onset. The patients were divided into two groups based on the presence or absence of CMBs and the two groups were adjusted using the pre-stroke modified Rankin scale (mRS). Poor outcome was defined as an mRS score in the 3–6 range measured 90 days after symptom onset. Logistic regression analyses were performed to determine the factors independently associated with poor outcome. Results— A total of 240 patients (187 men, median age 66 years old) were enrolled in our study. There was a non-significant trend toward a worsening shift of 3-month mRS score distribution in the CMB group compared with the no-CMB group. Multivariate analysis revealed that the presence of CMBs was independently predictive of poor outcome (OR, 3.44; 95% CI, 1.08–10.93; P = 0.036). Conclusion— Our findings suggest that the presence of CMBs is the predicting factor of poor outcome in minor ischemic stroke patients.